Pengaturan nutrisi tepat bagi atlet - Arimbi Arimbi; Abdul Rahman; Saharullah Saharullah (Seminar Nasional Pengabdian Kepada Masyarakat, 2018)
An athlete must have good stamina in supporting hisachievement improvement. Good stamina for an athlete can onlybe obtained if he consumes nutrients that are appropriate to theneeds of both during training and when competing. The body'sneed for nutrition is an absolute thing, nutrients needed tomaintain cell life in the body, both at rest and during exercise.All nutrients needed by the body are found in the food we eatevery day. The need for nutrients is absolute for the body to beable to carry out its normal functions. This energy is obtainedfrom the food eaten by a swimming athlete on a daily basis. Theright food will be able to produce good physical conditionsbecause the food will provide energy that is in accordance withthe needs of his body in his daily life.